A cross-sectional assessment of the relationship between sedative medication and anticholinergic medication use and the movement behaviour of older adults living in residential aged care - Gaynor Parfitt; Dannielle Post; Lisa Kalisch Ellett; Renly Lim; Alison Penington; Megan Corlis; Elizabeth Roughead (PeerJ, 2020)
Objectives Medications with anticholinergic or sedative effects are frequently used by older people but can increase risk of falls and adverse events; however, less is known about their effect on movement behaviour. Here we examine the cross-sectional association between medication use and movement behaviour in older adults living in residential aged care. Materials and Methods Twenty-eight older adults living in residential aged care in metropolitan Australia participated. Medication data were collected from participants’ medical charts and sedative load and anticholinergic burden were determined. Seven-day movement behaviour was objectively assessed by a wrist-worn triaxial accelerometer. Raw accelerations were converted to sleep, sedentary time, and time in light, moderate, and moderate-to-vigorous physical activity. To explore the relationship between medication and movement behaviour, Spearman’s Rho correlations were conducted, as the data were not normally distributed. Results Analyses indicated that while anticholinergic burden was not associated with movement behaviour, sedative load was negatively correlated with a number of variables, accounting for 14% variance in moderate-to-vigorous physical activity (MVPA), and 17% in the bout length of MVPA (p < .02). Conclusion The findings of this study showed a negative association between sedative load, due to medicines, and an individual’s movement behaviour. The impact of this could be a reduction in the ability of this population to maintain or improve their functional mobility, which may overshadow any benefits of the medicine in some circumstances.